(3GdMeGjI GdLfGFjI dMb GdEfSGf ai UhQJg (B/ s - (3eMeO habi YHOGdeLjO NjQ Gddgs; (3YeQ eMeO eMeO SGdes; (3eCehf eMeO SdGeI s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2019)
(3JfGhd GdHMK GdMeGjI GdbGfhfjI ddMjGI GdNGUI YfO GdeSGS HgG Yf WQjb GdUhQI(B: (3h YQafG cja HOCJ gPg GdMeGjI MeGjI eOfjI(B: (3Ci Yf WQjb fUhU GdbGfhf GdeOfj(B: (3Ke XgQ GJLGg jfGOi HYOe caGjI gPg GdMeGjI GdeOfjI(B: (3aJONd GdeTQY GdLfGFj(B: (3aCVai MeGjJg Ydi GdMb aj GdUhQI(B: (3Ke JYQVJ GdQSGdI deVehf gPG GdMb h NUGFUg hGdSdWGJ GdJj jefMgG(B: (3h GdJejjR Hjfg h Hjf ZjQg ef GdMbhb GdCNQi GdeJTGHgI(B: (3cGdMb aj GdGSe(B: (3h GdMb aj GdUhJ(B: (3h GdMb aj GdeYdheGJ(B: (3h GdMb aj GdSQ(B: (3h GdMb aj GdTQa h GdGYJHGQ(B. (3ZjQ Cf LGfHkG ef Gdabg h GdbVGA QCi Cf dgPG GdMb WHjYI eROhLI(B: (3h bO afOJ GdOQGSI gPG GdQCj h GdCSHGH GdJj OYJ Edjg(B: (3ef ZehV GdMb aj GdUhQI h GQJHGW GdMb aj GdUhQI HGdMb aj GdMjGI GdNGUI h GSJZdGd GdTNU dUhQJg(B. (3Ke JWQb GdHMK HYO Pdc ddJcjja GdbGfhfj dMb GdTNU aj UhQJg(B: (3h bO KHJ dOi GdHGMK Cf gPG GdMb(B: (3Mb eSJbd(B: (3HYO Cf hVYfG dg GdeYjGQ GddGRe ddaUd Hjfg h Hjf GdMb aj GdMjGI GdNGUI (B((3eYjGQ GdfJjLI GdELQGejI(B) (3gPG h bO JYQVJ GdOQGSI dfWGb GdMb Ydi GdUYjOjf GdJTQjYj h Gdabgj(B: (3aYdi GdUYjO GdJTQjYj QCjfG cja GJNP GdeTQY (B"(3GdecGf GdNGU(B" (3eYjGQkG dJMOjO fWGb GdMeGjI GdLfGFjI(B: (3CeG Ydi GdUYjO Gdabgj(B: (3abO QCi GdHYV GdJhSY aj fWGb GdMeGjI GdLfGFjI dgPG GdMb djeJO Edi MeGjI GdTNU aj ecGf YGe(B. (3h EVaGA GdMeGjI GdLfGFjI Ydi UhQI GdehOjd h GdejfcGf h GdcGQjcGJjQ HGdEVGaI Edi GdeWGdHI HJMbjb GdJhGRf Hjf GdMb aj GdEYdGe hGdMb aj GdUhQIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2019s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B625-676s
(3GdfU HGdYQHjI hGdedNU HGddZI GdaQfSjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdMb ai GdUhQIs; (3GdMeGjI GdLfGFjIs; (3Mb GdEfSGfs; (3GdWHjYI GdbGfhfjI GdeROhLI s; (3GdCMcGe GdehVhYjIs; (3LQGFe GdGYJOGA Ydi Mb GdTNUs; (3QSGFd LGeYjI s -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs